A novel proton conducting ionogel electrolyte based on poly(ionic liquids) and protic ionic liquid. (20th June 2020) - Rao, Jun; Wang, Xiaoen; Yunis, Ruhamah; Ranganathan, Vijayraghavan; Howlett, Patrick C.; MacFarlane, Douglas R.; Forsyth, Maria; Zhu, Haijin
Abstract: As opposed to the traditional hydrogels and organogels, ionogels are a new class of gel family where the liquid phase, percolating through the solid phase, consists of an ionic liquid (IL). The properties inherent in the ionic liquids, including high ionic conductivity, low-volatility and wide electrochemical stability window, are imparted to the ionogels. In this work, a novel proton conducting ionogel polymer electrolyte (iGPE) based on a poly (ionic liquid) Poly(diallyldimethylammonium) bis(trifluoromethanesulfonyl)imide, ([PDADMA][TFSI]) and protic ionic liquid, N, N -diethylmethylammonium triflate ([DEMA][Tf]) is prepared. The influence of the protic ionic liquid content on the physical, electrochemical, and ion transport properties of the iGPE has been investigated by differential scanning calorimetry (DSC), electrochemical impedance spectroscopy (EIS), and multi-nuclear solid-state and pulse-field gradient nuclear magnetic resonance. Upon addition of 60 wt% protic IL, the conductivity of the iGPE can be enhanced to 5.8 mS/cm at 100 °C, which is signifiantly higher than that of Nafion at 120 °C (0.2 mS/cm). Solid-state and PFG NMR measurements show that although the incorporation of [PDADMA][TFSI] leads to decreased ion dynamics, it promotes proton dissociation, resulting in a lower activation energy for ion diffusion compared to the neat protic IL. Evidence of proton activity in the iGPEs was obtained by cyclic votammetry, making this material a promising candidate as a proton conducting membranes in fuel cell applications. Graphical abstract: Image 1